2010
DOI: 10.1002/jbmr.63
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional evidence of suppressed bone mineral accrual among female adolescent runners

Abstract: We aimed to evaluate patterns of bone mineral accrual among a cross-sectional sample of female adolescent runners and girls participating in a nonendurance running sport. One-hundred and eighty-three interscholastic competitive female athletes (age 16.0 AE 0.1 years), 93 endurance runners and 90 nonrunners, completed a menstrual and sports history questionnaire, had their height and weight measured, and underwent a dual-energy X-ray absorptiometry scan for the measurements of body composition and bone mass. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…Long-distance runners are at a higher risk of sustaining stress injuries to bone as a result of their high training volume (and thus increased exposure of bone to repeated stress), potential biomechanical imbalances (such as pes planus, leg length discrepancy, or increased Q angle), 19,54 and risk of undernutrition. 5,6,20,38 Of the 34 athletes with bone stress injuries in this study, 22 (65%) were female ( Table 2), suggesting that women in the study were at higher risk. Multiple prior studies have reported similar findings.…”
Section: Nattiv Et Almentioning
confidence: 77%
“…Long-distance runners are at a higher risk of sustaining stress injuries to bone as a result of their high training volume (and thus increased exposure of bone to repeated stress), potential biomechanical imbalances (such as pes planus, leg length discrepancy, or increased Q angle), 19,54 and risk of undernutrition. 5,6,20,38 Of the 34 athletes with bone stress injuries in this study, 22 (65%) were female ( Table 2), suggesting that women in the study were at higher risk. Multiple prior studies have reported similar findings.…”
Section: Nattiv Et Almentioning
confidence: 77%
“…Researchers and expert working groups have previously concluded that in comparison with adults, children and adolescents are less effective in regulating body temperature and have lower exercise tolerance in the heat (Bar-or et al, 1980;Council on Sports Medicine and Fitness, 2000;Drinkwater et al, 1977;SMA, 2008). The reasons for these differences include:…”
Section: Fluid Recommendations For Adolescent Athletesmentioning
confidence: 97%
“…There appears to be a dose-response relationship between energy availability and markers of bone turnover in exercising females [ 45 ] and bone turnover markers are lower in athletes with amenorrhea [ 40 ]. Distance runners seem to be at especially high risk for inadequate bone mass accrual as a cross-sectional study of female adolescent runners showed no signifi cant difference in bone mineral content between runners ages 13-14 and 17-18, which was in contrast to non-runners who had normal increase in bone mineral content with age [ 46 ]. Additionally, as the number of risk factors for the Triad increases, there is a greater risk of low bone mineral density [ 47 ].…”
Section: Discussionmentioning
confidence: 52%